Country risks analysis for the development of green hydrogen and synthetic fuel sectors in the MENA region - Terrapon-Pfaff, Julia; Ersoy, Sibel Raquel; Prantner, Magdolna; Viebahn, Peter (Frontiers in Energy Research, 2024)
Hydrogen is vital for decarbonizing global energy and industry. The EU, particularly Germany, expects to rely on significant hydrogen imports in the medium to long term, with the Middle East and North Africa (MENA) region identified as a key potential green hydrogen producer and exporter. Investment risks play a critical role for advancing the green hydrogen and synthetic fuels sectors in the region But comparative analyses of country risks for the renewable energy sector across the MENA region, as well as country risk assessments for the development of a green hydrogen sector and downstream synthetic fuel sectors, are lacking. To address this research gap the present study conducts a comparative analysis of risks for the (further) development of the renewable energy sector and the green hydrogen and synthetic fuel sector in seventeen MENA countries. To this end, a risk assessment framework was developed that takes into account macro and micro risks and was applied to 17 countries in the MENA region. In order to consider future developments in addition to assessing the current situation, two further contrasting risk scenarios were developed. These risk scenarios show how country risks could evolve in the future if macro and micro risks are reduced or heightened. Overall, the results show that the development of the green hydrogen and synthetic fuels sector in almost all MENA countries studied is associated with at least moderate risks. hat gelöscht: Hydrogen is considered a central building block for 37 decarbonising the global energy and industry systems. To meet the 38 projected demand the European Union as a whole and selected 39 member states, particularly Germany, foresee that in the medium to 40 long term, substantial quantities of hydrogen will need to be 41 imported. The Middle East and North Africa (MENA) are frequently 42 highlighted as potential future producers and exporters of green 43 hydrogen. For the development of the green hydrogen and synthetic